2010
DOI: 10.1111/j.1463-1318.2010.02356.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of right- and left-sided colonic and rectal cancer following surgical resection

Abstract: Right-sided colorectal cancers had a worse prognosis than left-sided and rectal cancers, possibly because of more advanced staging and fewer curative resections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 23 publications
1
59
2
1
Order By: Relevance
“…179,182 However the distance between colon and rectal cancer became enormous due to the progresses both in surgical and preoperative therapy.…”
Section: Lymphatic and Venous Invasionmentioning
confidence: 99%
“…179,182 However the distance between colon and rectal cancer became enormous due to the progresses both in surgical and preoperative therapy.…”
Section: Lymphatic and Venous Invasionmentioning
confidence: 99%
“…The physiologic basis for this argument may lie in the fact that the right and left colon have different embryologic origins, microenvironments, and distinct blood supplies. Subsequently, there has been growing evidence that right-sided colon cancer (RC) and left-sided colon cancer (LC) represent distinct entities [3,4], with differences observed in epidemiology, biology, pathology and clinical outcomes [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Most, but not all studies have found poorer survival with RsCC [711]. A recent meta-analysis found a statistically significant worse overall survival in patients with RsCC, although there was significant heterogeneity seen due the spectrum of included study designs, disease stage, and limited information about treatment received by patients [12].…”
Section: Introductionmentioning
confidence: 99%